The C-Terminal Domain of Thrombomodulin Regulates Monocyte Migration with Interleukin-6 Stimulation. (January 2014) - Lin, Y.W.; Huang, C.Y.; Shih, C.M.; Chang, W.L.; Shyue, S.K.; Tsai, Y.T.; Lin, C.Y.; Lee, C.Y.; Chang, Y.J.; Chang, N.C.; Lin, F.Y.; Tsai, C.S.
Thrombomodulin (TM) is expressed on the surface of monocyte, which is important in the regulation of cell migration, proliferation, and inflammatory responses. In a previous study, we demonstrated that TM on monocyte is negatively associated with cell migration. However, the mechanisms involved in this process are unclear, therefore, we explored the mechanisms in this study. Chemotactic assays and immunofluorescence showed that TM siRNA increased the Chemotaxis of the IL-6-activated THP-1, and aggravated actin assembly relative to the IL-6-treated control. In contrast, cells overexpressing plasmids containing full-length or domain 5 of TM followed by IL-6 treatment displayed lower Chemotaxis and less actin assembly. Western blot analysis showed that TM knockdown markedly increased cytoskeleton components cofilin and LIMK1 phosphorylation in IL-6-treated THP-1, whereas, transfected cells with HA-TM FL or HA-TM D5, but not HA-TM Dl-3 plasmids, reversed the effects. Activation of ERK1/2 and JNK/SAPK, upstream regulators of cytoskeleton components, were also inhibited in overexpressed group. Immunoprecipitation assay demonstrated that actin interacts with TM and intersectin1 in THP-1. Decreased interaction between intersectin1 and actin in TM knockdowns suggested that the interaction is mediated by TM. Our findings indicate that TM domain 5 is a negative regulator and seems to have the ability to inhibit paxillin, cofilin, LIMK1, and actin activation. The mechanisms for the repression effect of domain 5 may be mediated by inhibition of the ERK1/2 and JNK/SAPK activation. Expression of domain 5 of TM may represent a promising approach for controlling monocyte migration, and TM may have potential applications in treatment of inflammatory diseases.